The CERTAIN Study Results: Adjunctive p16 Immunohistochemistry Use in Cervical Biopsies According to LAST Criteria. (1st October 2021) - Wright, Thomas C.; Stoler, Mark H.; Ferenczy, Alex; Ranger-Moore, James; Fang, Qijun; Kapadia, Monesh; Singh, Shalini; Ridder, Ruediger
Abstract : Supplemental Digital Content is available in the text. Abstract : The Lower Anogenital Squamous Terminology (LAST) Project recommends the use of p16 immunohistochemistry as an adjunct to morphologic assessment of cervical biopsies according to a specific set of criteria. We analyzed the effect of adjunctive p16 according to LAST criteria in a US-based diagnostic utility study involving 70 surgical pathologists providing a total of 38, 500 reads on cervical biopsies. Compared with the results obtained using hematoxylin and eosin-stained slides only, including p16-stained slides per LAST criteria increased sensitivity and specificity for diagnosing histologic high-grade squamous intraepithelial lesions across all cases by 8.1% (95% confidence interval [95% CI], 6.5-9.7; P <0.0001) and 3.5% (95% CI, 2.8-4.2; P <0.0001), respectively, using expert consensus diagnoses on hematoxylin and eosin+p16 as reference. Within the subset of cases classified by the pathologists as fulfilling the LAST criteria, adding p16 significantly increased both sensitivity (+11.8%; 95% CI, 9.5-14.0; P <0.0001) and specificity (+9.7%; 95% CI, 7.8-11.5; P <0.0001). However, a comparable improvement in sensitivity (+11.0%; 95% CI, 7.8-14.1; P <0.0001) was found when p16 was used in cases for which p16 staining was not ordered per LAST by the pathologists, whereas specificity decreased by −0.8% (95% CI, −1.1 to −0.5; P <0.0001). The study demonstrates a clinically and statistically significant increase in sensitivity and specificity for high-grade squamous intraepithelial lesion when p16 is used according to LAST criteria. Expanding the use of p16 into non-LAST cases would lead to a comparable improvement in sensitivity within this subgroup of biopsies, at the cost of a minimal, but statistically significant difference in specificity.